Masyarakat Muslim di Bali : Dari Kawula hingga Warganegara - Eddy Setiawan (Institut Kewarganegaraan Indonesia, 2023)
The arrival of outsiders with different religious and cultural backgrounds during Bali’s classical era was equally recognized as the local subjects. The patron-client relationships during this period led to a tendency towards cultural acculturation and, to some extent, spiritual syncretism which shaped Muslim-Bali. In the colonial era, the Dutch then took the position of patron from the Puri, separating Balinese and non-Balinese through desa adat and dinas. Meanwhile, the development of Islamic education has led to orthodoxy, thus completely separating the two communities. Muslim immigrants after this process are called Muslims Baru. Desa dinas had a better position during the colonial to the New Order period. However, with the decentralization process, desa dinas have become mere administrations with weak political bargaining. Balinese-Muslim and Muslims Baru citizenship seems to have to deal with a new form of citizenship in the name of customary tradition, between krama wed, krama tamiu, and tamiu. Non-Balinese Hindu citizens are classified as tamiu in the context of desa adat. Therefore, in terms of participation and redistribution, indigenous communities have a better position than those in dinas. Similarly, Balinese-Muslims have a better position because of the autonomous power through their “desa adat”. Meanwhile, Muslims Baru without “desa adat” are only members of administrative desa dinas, with limited participation, thus affecting the redistribution aspect.